2018
DOI: 10.1155/2018/9571828
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Ammonia-Modified Graphene Oxide Particles in Lung Cancer Cells and Embryonic Stem Cells

Abstract: Potential toxicity of graphene oxide (GO) is a subject of increasing research interest in the recent years. Here, we have evaluated the cytotoxicity of ammonia-modified GO (GO-NH2) and pristine GO particles in human lung cancer cells, A549 and embryonic stem cells, Lep3 exposed to different particles concentrations (0.1, 1, 10, 20, and 50 μg/ml) for different times (24 and 48h). Compared with GO, GO-NH2 particles possessed smaller size, positive surface charge and higher thickness. An increased propensity to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Compared with pristine GO, haGO-NH 2 sheets were more wrinkled (the right micrograph at Figure 2A) with no other morphological changes being detected. Similar morphologies for both, pristine and aminated by ammonia GO sheets have been observed in our previous studies [21], indicating that the different methods of amination of GO resulted in a similar effect on GO morphology, namely increasing the level of crumpling of the modified GO sheets. Dynamic light scattering (DLS) is a particularly important technique for determining nanoparticle size and size distribution in aqueous suspensions.…”
Section: Structural and Biophysical Characterization Of Go And Hago-nsupporting
confidence: 86%
See 1 more Smart Citation
“…Compared with pristine GO, haGO-NH 2 sheets were more wrinkled (the right micrograph at Figure 2A) with no other morphological changes being detected. Similar morphologies for both, pristine and aminated by ammonia GO sheets have been observed in our previous studies [21], indicating that the different methods of amination of GO resulted in a similar effect on GO morphology, namely increasing the level of crumpling of the modified GO sheets. Dynamic light scattering (DLS) is a particularly important technique for determining nanoparticle size and size distribution in aqueous suspensions.…”
Section: Structural and Biophysical Characterization Of Go And Hago-nsupporting
confidence: 86%
“…PEGylation reduces the non-specific binding of GO to biological membranes and improves its in vivo pharmacokinetics for better tumor targeting [18,19]. In our previous study, we found that exposure to ammonia-modified GO NPs could induce cell cycle arrest in the G2/M phase, thus, significantly increasing the apoptosis rate and the generation of reactive oxygen species (ROS) in colorectal Colon 26 and lung A549 cancer cells, but did not influence the viability of non-tumor embryonic stem cells [20,21]. Our findings highlight the potential of GOs NPs to be used as anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The non-tumor embryonic stem cell morphology was strongly influenced, whereas cancerous A549 cells better withstood short-term exposure. After 48 h of exposure, the embryonic stem cells proliferative ability remained unaffected and, on the contrary, a strong effect on A549 cell proliferation was demonstrated [63].…”
Section: Cytotoxicity and Biocompatibilitymentioning
confidence: 91%
“…Previous studies have shown that the information obtained on the in vitro and in vivo toxicity of GBMs due to their dimensions and variation in oxidation states is far from complete [60]. The interactions of living cells with GBMs depends on their hydrophilicity, surface chemistry, purity, lateral dimensions, layer number, and dose [61][62][63][64]. These properties vary greatly according to their synthesis eventually to methods of functionalization.…”
Section: Cytotoxicity and Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation